THE 1972-1974 ERUPTION OF KLYUCHEVSKOY VOLCANO, KAMCHATKA - Ivanov B.V.; Gorelchik V.I.; Andreev V.N.; Maksimov A.P.; Stepanov V.V.; Chirkov A.M. (My University, 1981)
A new Klyuchevskoy volcano eruptive cycle encompasses terminal (March 30, 1972 to August 23, 1974) and lateral (August 23, 1974 to December, 1974) eruption stages. The terminal eruption stage resulted in lava flows and parasitic cones that formed on the south-western flank of the volcano.Eruption products are moderately alkalic high-alumina olivine-bearing andesite-basalts. The terminal eruption stage was accompanied by volcanic earthquakes and volcanic tremor. The lateral eruption was accompanied by explosive earthquakes. Volcanic tremor was the most useful prognostic sign indicating the onset of the lateral eruption. Eruptive mechanisms are discussed.
Keywords: 38.37.25 Вулканология; Ключевской